2020
DOI: 10.1093/cdn/nzaa084
|View full text |Cite
|
Sign up to set email alerts
|

Towards Population Salt Reduction to Control High Blood Pressure in Ghana: A Policy Direction

Abstract: Although population salt reduction is considered a ‘best buy’ in addressing hypertension and cardiovascular disease, Ghana shares a high hypertension burden with a seemingly high salt consumption. This paper discusses best practices in reducing population salt intake and preliminary data on salt and potassium intake, and the process to develop a road map and identification of actions needed to support the development of a strategic national document towards salt reduction in Ghana. In February 2019, a two-day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…While African regions in general are reported to have lower sodium intake compared to other world regions, the average amount consumed across all African regions is above the WHO recommended intake guidelines (1,3). Where studies have assessed intake in specific African countries, the reported salt intake is more comparable or above to the mean global intake level of 9-10 g/day (4)(5)(6)(7)(8)(9). Furthermore, sodium intake is likely to rise in African populations in the future (similar to other developing countries) as dietary patterns transition to a higher proportion of processed and convenience foods (10,11).…”
Section: Dietary Sodium Intake and Bouillon In Sub-saharan Africa Afr...mentioning
confidence: 92%
“…While African regions in general are reported to have lower sodium intake compared to other world regions, the average amount consumed across all African regions is above the WHO recommended intake guidelines (1,3). Where studies have assessed intake in specific African countries, the reported salt intake is more comparable or above to the mean global intake level of 9-10 g/day (4)(5)(6)(7)(8)(9). Furthermore, sodium intake is likely to rise in African populations in the future (similar to other developing countries) as dietary patterns transition to a higher proportion of processed and convenience foods (10,11).…”
Section: Dietary Sodium Intake and Bouillon In Sub-saharan Africa Afr...mentioning
confidence: 92%
“…The procedure has been used as a knowledge translation strategy for health systems research in Africa [9]. In Ghana and in South Africa, process mapping has been used as a strategy to combat lung cancer and hypertension [10,11]. Our approach was novel because process mapping has been used to shape policy change in population health, but has never been used to analyze neurological care.…”
Section: Methodsmentioning
confidence: 99%
“…Notwithstanding, the implementation of social and behavior change communication solely will not reduce dietary sodium intake to the recommended levels [ 65 ] in African countries because of the relationships of sodium intake with various aforementioned environmental factors. It is essential to incorporate families, communities, community organizations, industry leaders, and government stakeholders in policy development [ 66 ] when developing multi-level intervention strategies to reduce sodium intake among populations.…”
Section: Ebis That Can Mitigate Sodium Intake and Impact The Downstre...mentioning
confidence: 99%